A high durable polysaccharide flame retardant based on phosphorus element for cotton fabrics. (April 2023) - Lu, Yanfeng; Ding, Dan; Liu, Yunlan; Lu, Yonghua; Zhang, Fengxiu; Zhang, Guangxian
Highlights: The flame retardant (DOPSAP) has relative high molecule based on polysaccharide and introducing more p element through P-C bonds. DOPSAP is an environmentally friendly flame retardant. The flame retardant grafted on cellulose through P–O–C covalent bonds. Cotton treated with DOPSAP has high flame retardant and durability, could pass AATCC 61–2013 3A standard 50 LCs. DOPSAP mainly exhibited a condensed phase flame retardant mechanism. Abstract: A novel polysaccharide flame retardant 2, 6-dimethoxy polysaccharide ammonium phosphate (DOPSAP), was synthesized and characterized using nuclear magnetic resonance (NMR) and Fourier-transform infrared (FT-IR) spectroscopy. The characterization results of cotton samples suggested that DOPSAP was successfully grafted onto the cotton fabric through P-O-C covalent bonds. The char length and limiting oxygen index (LOI) of cotton fabrics treated with 30 wt% DOPSAP were 42 mm and 49.4%, and remained at 52 mm and 37.5% after 50 LCs in the violent washing conditions (AATCC 61–2013 3A washing standard), respectively. These results indicated that cotton fabrics treated with DOPSAP had excellent flame retardancy and durability. In the thermogravimetric (TG) analysis, the treated cotton retained 40.8% of the char residual at high temperature under N2 atmosphere. The total heat release (THR) of DOPSAP-treated cotton fabrics reduced from 4.2 to 2.1 MJ/m 2 compared to untreated cotton fabrics in the cone calorimetry test. These results showed that DOPSAP inhibited the heat release of cotton fabrics during combustion by promoting the dehydration of cotton fabrics to produce more char, exhibiting a cohesive phase flame-retardant mechanism. The mechanical properties of the treated cotton fabric were remained well. The results showed that the flame retardant with relative high molecule based on polysaccharide and introducing more P element through P-C bonds are effective ways to improve the durability and flame retardancy of treated cotton.